Anthropology of the South American Lowlands - Combes de Guzman, Isabelle (2020)
Since the first contacts, the ’lowlands’ of South America have been defined in a residual way, as the term referred to all the regions that do not belong to the Andes: the immense Amazon, the Chaco, Patagonia and the Atlantic coast. In fact, the lowlands were thought of as a sort of negative image of the picture that Andean societies presented to the conquistadores: like Central America, with its kings and nobles, its numerous armies, its productive surpluses and its monumental constructions, the Andes and its inhabitants offered an exotic image, certainly. But it was also one that was more understandable or, at the very least, easier to identify: the image of a consolidated state, of farming and sedentary peoples, with a certain demographic density, and more familiar to Europeans. Therefore it is not surprising that in trying to understand the peoples who lived east of the Andes, beyond the Piedmont, European observers most often recycled the prejudices, generic categories and stereotypes of savagery or barbarity that were held by the Andean peoples themselves, who thought of the peoples of the lowlands through the reductive prism of the ’Anti’, the ’Chuncho’ or the ’Chiriguano’ – all generic and contemptuous terms, equivalent to our ’savages’ or ’barbarians’.